EU law stories : contextual and critical histories of European jurisprudence - Nicola, Fernanda, 1972-; Davies, Bill, 1979- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2017)
"Through an interdisciplinary analysis of the rulings of the Court of Justice of the European Union, this book offers 'thick' descriptions, contextual histories and critical narratives engaging with leading or minor personalities involved behind the scenes of each case. The contributions depart from the notion that EU law and its history should be narrated in a linear and incremental way to show instead that law evolves in a contingent and not determinate manner. The book shows that the effects of judge-made law remain relatively indeterminate and each case can be retold through different contextual narratives, and shows the commitment of the European legal elites to the experience of legal reasoning. The idea to cluster the stories around prominent cases is not to be fully comprehensive, but to re-focus the scholarship and teaching of EU law by moving beyond the black letter and unravel the lawyering techniques to achieve policy results."--
Introduction to EU law stories : contextual and critical histories in European jurisprudence / Bill Davies and Fernanda Nicola -- EU law classics in the making : methodological notes on Grands arrets at the European Court of Justice / Antoine Vauchez -- Behind the scenes at the Court of Justice : drafting EU law stories / Karen McAuliffe -- Judges or hostages? : sitting at the Court of Justice of the European Union and the European Court of Human Rights / Mathilde Cohen -- Imagining the course of European law? : Parti Ecologiste 'Les Verts' v. Parliament as a constitutional milestone in EU Law / Anne Boerger and Bill Davies -- Law meets history : interpreting the van Gend en Loos judgment / Morten Rasmussen -- Goodbye to all that : Commission v. Luxembourg and Belgium, and European Community law's break with the enforcement mechanisms of general international law / Will Phelan -- Acts of creation : the ERTA decision as a foundation stone of the EU legal system / Anne McNaughton -- Internationale handelsgesellschaft and the miscalculation at the inception of the ECJ's human rights jurisprudence / Bill Davies -- Personal conviction and strategic litigation in Wijsenbeek / John Morijn -- Breaking Chinese law : making European one : the story of Chen; or two winners, two losers, two truths / Dimitry Kochenov and Justin Lindeboom -- Ruiz Zambrano's quiet revolution : four hundred and sixty-eight days that made the immigration case of one deprived worker into the constitutional case of two precarious citizens / Francesca Strumia -- Media pluralism in Centro Europa 7 Srl, or when your competitor sets the rules / Roberto Mastroianni -- The difficult quest to implement cartel control : Grundig-Consten (1966) and Philip Morris (1987) / Laurent Warlouzet -- The Cassis legacy : kir, banks, plumbers, drugs, criminals and refugees / Kalypso Nicolaidis -- The duty of sincere cooperation as lawyering strategy : a personal account of Commission v. United Kingdom case 804/79 / John Temple Lang -- Centros, the freedom of establishment for companies, and the court's accidental vision for corporate law / Martin Gelter -- The pyrrhic victory of Mr. Francovich and the principle of state liability in the Italian context / Antonio Bartolini and Angela Guerrieri -- Tessili v. Dunlop 1976 : the political background of judicial restraint / Vera Fritz -- r Jenkins v. Kingsgate and the migration of the US disparate impact doctrine in EU law / Ioanna Tourkochoriti -- Mademoiselle Gravier and equal access to education : success and boundaries of European integration / Gisella Gori -- The early retirement age of the Hungarian judges / t
Includes bibliographical references and index.
Keywords: European Union; Law -- European Union countries -- Cases; Jurisprudence -- European Union countries -- History; European law; International administration of justice: general; Jurisprudence; Law; European Union; Case-law.; Cases; History; Community law; European Union countries; History; Trials, litigation, etc